A Study to Evaluate the Effectiveness of Structured Educational Package on Knowledge Regarding Oral Hygiene among Primary Schoolchildren Studying in Selected Schools, Karnataka, India. - Joseph, Nice; Biju, Bincy; George, Feba; Mohanan, Haritha; John, Linu; Harikantra, Padma; Naik, Pratiksha; Naik, Sheetal (International Journal of Nursing Research, 2023)
Background: The oral health is a fundamental part of the general health and well-being of an individual. It can be achieved by maintaining a good oral hygiene. Oral hygiene is the individual habit and professional methods used to control the bacterial biofilm (dental plaque) that grows on the tooth surface. If not removed regularly, dental plaque can lead to tooth decay and cause periodontal diseases. Aim: This study aims to evaluate the effectiveness of structured educational package on knowledge regarding oral hygiene among students in selected schools, Karnataka. Methods: An evaluative approach with true experimental pretest-posttest design was used for the study. Twenty-eight primary schoolchildren were selected in control group from the practicing primary school and 25 primary schoolchildren were selected in the experimental group from the Nirmala Hridaya English Medium School, Ankola. The data were collected by the structured questionnaire which is designed to assess the knowledge regarding oral hygiene. The structured questionnaire consists of two sections. Section A consists of 6 items related to demographic data and Section B consists of 25 items related to knowledge regarding oral hygiene. A structured educational package was prepared and administered regarding oral hygiene after the administration of pre-test to the experimental group and post-test was conducted after 6 days of administration of structured educational package. The data collected were analyzed using descriptive and inferential statistics. Results: The findings revealed that in practicing primary school, the mean knowledge pre-test score was 11.928 and the mean post-test knowledge score was 12.35. In Nirmala Hrudaya English Medium School, the mean knowledge pre-test score was 8.8 and the mean post-test knowledge score was 14.24. Conclusion: The study findings revealed that there was a significant increase in knowledge level of primary schoolchildren after administration of the structured educational package.